Observations on Extended Distribution of New and Rare Taxa of North-Eastern India with Special Reference: to Arunachal Pradesh - Naithani, H. B.; Bahadur, K. N. (Indian Forester, 1981)
The paper presents observations made on extended distribution of 31 new and rare/endemic taxa of the north-eastern region of India during the course of the last few decades. New taxa here signify those species and varieties which have been described after the publication of Hooker’s Flora of British India. In most cases these taxa were known only by their type collections until they have been collected recently from outside their type localities, invariably from Arunachal Pradesh. These are: Agapetes similis, Albizia gamblei, Beilschmiedia pseudo-micropora, Crotalaria bhutanica, Dalbergia c1arkei, Dicentra paucinervia. Diospyrus cacharensis, Dysoxylum reticulatum, Gaultheria seshagiriana, Gomphogyne macrocarpa, Gymnocladus assamicus, Hydrocotyle himalaica, Indofevillea khasiana, Luculia grandfolia, Mitrephora harae, Paris polyphylla var. appendiculata, Phyllostachys assamica, Pinus bhutanica, Populus gamblei, Primula bhutanica, P. irregularis. P. scapigera, Rhodermachera siniea, Rhododendron dalhousiae var. Rhabdotum, Rhynchoglossum lazulinum, Salacia khasiona, Salix bhutanersis, Senedo baril, Spermacoce latifolia, Symplocos glauca and Syzygium assamicum. Besides, 3 new rare tree species viz. Albizia arunachalensis, Lithocarpus kamengensis and Rhudodendron tawangensis, which have recently been described from Arunachal Pradesh, are also highlighted. About 50% of these taxa have been collected after a lapse of 30 years or more. This fact as well as the other information contained in the paper given indication of the extent of rarity of these plants and would therefore help in taking measure to conserve them if necessary.